A Novel Method for Assessing Muscle Power During the Standing Cable Wood Chop Exercise. Issue 8 (August 2017) - Zemková, Erika; Cepková, Alena; Uvaček, Marián; Šooš, L'ubomír
Abstract : Abstract: Zemková, E, Cepková, A, Uvaček, M, and Šooš, L. A novel method for assessing muscle power during the standing cable wood chop exercise. J Strength Cond Res 31(8): 2246–2254, 2017—The study estimates the repeatability and sensitivity of a novel method for assessing (a) the maximal power during the standing cable wood chop exercise with different weights and (b) the endurance of the core muscles. A group of 23 fit men performed (a) maximal effort single repetitions of the standing cable wood chop exercise with weights increasing stepwise up to 1 repetition maximum (1RM) and (b) a set of 20 repetitions at a previously established weight at which maximal power was achieved. Results showed that mean power during the standing cable wood chop exercise is a reliable parameter, with intraclass correlation coefficient values above 0.90 for all weights tested. It was also shown to be a sensitive parameter able to discriminate within-group differences in the maximal power and endurance of core muscles. Substantial individual differences were found in mean power, especially at higher weights, and in the maximal power achieved at about 75% of 1RM (462.2 ± 57.4 W, n = 11), 67% of 1RM (327.2 ± 49.7 W, n = 7), and 83% of 1RM (524.0 ± 63.2 W, n = 5). At these weights, there were also significant differences between the initial and the final repetitions of the wood chop exercise (13.9%, p = 0.025; 10.2%, p = 0.036; and 13.8%, p = 0.028, respectively). These findings indicate that evaluation of the maximal power and endurance of the core muscles during the standing cable wood chop exercise on a weight stack machine is a reliable method and sensitive to differences among physically active individuals.